Motorboat noise can potentially mask the whistle sound of estuarine dolphins (Sotalia guianensis) - Albuquerque, Natalia de Souza; Souto, Antonio da Silva (Ethnobiology and Conservation, 2013)
Masking the sounds uttered by cetaceans is an important issue in underwater noise pollution produced by vessels. This research aimed to determine whether noises produced by the engines of tourism boats can mask whistles emitted by estuarine dolphins (Sotalia guianensis). Data collection was conducted at Baía dos Golfinhos (English: Dolphin Bay) (Rio Grande do Norte, Brazil), an area mainly used for foraging by these animals. We recorded underwater vocalizations of the animals and the sound generated by motorboats in the Bay using equipment capable of capturing sounds with frequencies up to 40 kHz. Sound amplitude was compared at 6, 10, 16 and 30 kHz. We also observed the boats activity in the area. The results showed that the noise produced by motorboats can reach frequencies of up to 40 kHz (average: petrol = 17.1 kHz, ± 8.4; diesel = 13.1 kHz, ± 4.9) and is similar to the whistles uttered by the estuarine dolphin (up to 35 kHz; average: 19 kHz, ± 6.2). The sound amplitude also reached similar values at the frequencies of 6, 10, 16 and 30 kHz for petrol engines, and 6 kHz for diesel motorboats (whistles were higher at 10 and 16 kHz). Thus, engine noise is a potential source of disturbance to the whistles uttered by these cetaceans. Even the presence of one tourism boat can potentially interfere with the communication between individuals and, as a consequence, on the performance of natural behaviours. Thus, our results can help to explain previous studies on estuarine dolphins that found behavioural disturbances in the presence of tourism boats. In addition, such findings are in accordance with a number of studies on other cetacean species that recorded negative impacts caused by motorboats. As a precautionary measure, a number of areas constantly used by the estuarine dolphins, such as the Baía dos Golfinhos, should be closed to motorboat traffic. This would minimize the negative impact caused by human activities on the welfare and conservation of the estuarine dolphins.